CCR5+ CD8 T-cell levels and monocyte activation precede the onset of acute coronary syndrome in HIV-infected patients on antiretroviral therapy - Tarancon-Diez, Laura; De Pablo-Bernal, Rebeca S.; Alvarez-Ríos, Ana I.; Rosado-Sánchez, Isaac; Dominguez-Molina, Beatriz; Genebat, Miguel; Pacheco, Yolanda M.; Jiménez, José Luis; Ángeles Muñoz-Fernández, M.; Ruiz-Mateos, Ezequiel; Leal, Manuel (Thrombosis and Haemostasis, 2017)
Acute coronary syndrome (ACS) is nowadays one of the leading causes of morbid-mortality in HIV-infected population, but innate and adaptive immune mechanisms preceding this event are unknown. In this work we comprehensively and longitudinally observed, by multi-parametric flow cytometry and following a case-control design, increased CCR5+CD8+ T-cells levels and monocytes expressing activation and adhesion markers in HIV-infected patients who are going to suffer ACS. In addition, we found direct associations between activated CD8+ T-cells and myeloid cells that were only statistically significant in the group of patients with ACS and in the follow up time point just before the ACS. Our data highlight the important role of CCR5 in the onset of ACS and suggest this receptor as a marker of cardiovascular risk and potential therapeutic target to prevent the development of such non-AIDS-related event in HIV-infected patients.Note: This work was presented at the CROI 2016 conference (Boston, USA in February 2016).
Keywords: HIV; CCR5; monocyte; vascular event; immune activation